HUBUNGAN ANTARA SCREEN TIME DENGAN POLA TIDUR PADA ANAK USIA 3 - 5 TAHUN DI MASA PANDEMI COVID-19 - Nareswari Izzaturrahman, (2022)
Screen time is defined as the time spent by a child to use screen-based media. Currently, the increase in screen time in children from year to year has experienced a significant increase, especially during the COVID-19 pandemic. Excessive use of screen-based media can have an impact on children's health both physically and emotionally, one of which is disturbed sleep patterns. This study aims to determine the relationship between screen time and sleep pattern disturbances that occur in children aged 3-5 years. This study used a cross sectional research design with a simple random sampling method. The sample in this study amounted to 86 children with the research instrument using the Children's Sleep Habits Questionnaire-Short Form (CHSQ). The results of the bivariate analysis using the Fisher Exact alternative test obtained a significant p-value of 0.0013 (<0.05) with an odds ratio (OR) of 4.197. Based on these results, it can be concluded that statistically there is a relationship between screen time and disturbed sleep patterns in children aged 3-5 years, where children with screen time > 1 hour per day have a 4.9 times greater risk of experiencing sleep pattern disorders than children with screen time 1 hour per day. This is because the blue light emitted by screen-based media will suppress the production of melatonin, a hormone that is indispensable in the process of sleep, so that when the hormone melatonin decreases, it will make it difficult for children to sleep and ultimately disrupt the child's sleep pattern.